Haemophilus somnus activation of brain endothelial cells: potential role for local cytokine production and thrombosis in central nervous system (CNS) infection - Behling-Kelly, Erica; Kim, Kwang S; Czuprynski, Charles J (Thrombosis and haemostasis, 2007)
Thrombotic meningoencephalitis (TME) is a neurological condition in cattle characterized by fibrinopurulent meningitis with hemorrhage, abscess formation and thrombotic vasculitis throughout the central nervous system. The etiologic agent of TME is Haemophilus somnus, a gram-negative pleomorphic coccobacillus. Although the pathogenesis of TME is not well understood, the propensity of H. somnus to cause vasculitis and intravascular thrombosis suggests a critical role for the interactions between the bacteria and endothelial cells in inciting the disease. The goal of this study was to determine if H. somnus elicits an inflammatory and procoagulative response in bovine brain microvascular endothelial cells (BBEC) in vitro. We demonstrate that BBEC exposed to H. somnus secrete significant levels of the proinflammatory and procoagulative cytokines TNF-alpha and IL-1beta. BBEC treated with H. somnus also display increased levels of IL-6 mRNA, another cytokine associated with coagulopathy in vivo. H. somnus-treated BBEC exhibited increased procoagulant activity and tissue factor expression and activity, along with a decreased ability to activate protein C and decreased expression of thrombomodulin mRNA. These changes would be expected to promote thrombus formation in vessels of the CNS, and potentially contribute to the pathogenesis of TME.